Pengaruh Economic Value Added (EVA) Dan Market Value Added (MVA) Terhadap Return Saham Pada Perusahaan Sub Sektor Otomotif Di Bursa Efek Indonesia (BEI) - Ayu Lestari; Muhamad Rimawan (EBISMAN eBisnis Manajemen, 2023)
This research aims to examine Economic Value Added (EVA) and Market Value Added (MVA) on Stock Returns in Automotive Sub-Sector Companies on the Indonesia Stock Exchange (BEI). This type of research includes associative research using secondary data obtained from financial reports on the website www.idx.co.id. The population in this research is the financial reports of 16 automotive sub-sector companies listed on the Indonesian Stock Exchange. The method used in selecting the sample was purposive sampling and determining the sample based on criteria established by the researcher with the results of the financial reports of 3 automotive sub-sector companies during the period 2018 - 2022. Based on the results of data processing using the multiple linear regression analysis method, F test, test t, it is known that there is a partially significant influence of EVA on stock returns, there is a partially significant influence of MVA on stock returns and there is a simultaneous significant influence of EVA and MVA on stock returns.